Analisis Peran Orang Tua dalam Memotivasi Belajar Siswa pada Masa Pandemi di Kelas III SD Tiranus Pondok Kopi - Agnes Tasiah Yuninda; Rudi Ritonga (Departement of Mathematics Education, 2023)
This researcher is related to the role of parents in student motivation during the pandemic, researchers found problems related to the decline in student learning motivation in online learning in using google meet and whatsapp groups, namely students lack of concentration, lack of teacher interaction with students because the learning process only exists one direction and the absence of reciprocity so that the learning atmosphere is very boring and makes students passive. The purpose of this study was to determine the role of parents and the obstacles faced in motivating student learning during the third grade pandemic at SD Tiranus Pondok Kopi. This study uses a qualitative method with a descriptive method. The results of the research on the role of parents are very important for children because they are still not independent in learning to dare and parents as motivators. Efforts on the role of parents in learning motivation have been carried out well, parents always try to increase children's learning motivation by accompanying children, supervising children's learning activities, giving awards.